PREDICTION OF DURABILITY OF ADHESIVE JOINTS OF OAK TIMBER BY POLYVINYL ACETATE-BASED ADHESIVES - Kshyvetskyy , Bogdan; Bekhta , Pavlo (Forestry, Forest, Paper and Woodworking Industry, 2024)
On the basis of long-lasting researches in vivo (within three months) on changes in strength of adhesive joints of oak timber by polyvinyl acetate-based adhesive there was worked out a mathematical model and chart allowing to predict the durability of joints of wood. It provides the possibility using the non-destructive method to predict the durability of adhesive joints of wood during its exploitation under the influence of natural factors.